Transpulmonary plasma catecholamines in acute high-altitude pulmonary hypertension - Berger, Marc Moritz; Luks, Andrew M.; Bailey, Damian M.; Menold, Elmar; Robotti, Guido C.; Mairbäurl, Heimo; Dehnert, Christoph; Swenson, Erik R.; Bärtsch, Peter (Wilderness & environmental medicine, 2011)
Objective - High altitude leads to an increase in sympathetic nervous system (SNS) activity and pulmonary arterial pressure (PAP). We assessed whether the SNS contributes to this increase in PAP. - Methods - Sympathetic discharge to the pulmonary vasculature was assessed by measuring plasma norepinephrine concentrations in central venous blood entering the lung and systemic arterial blood leaving the lung (arterial-central venous difference; a − cvdiff). Sympathetic activity in the adrenal gland was assessed by measuring systemic plasma epinephrine concentrations. The a − cvdiff of epinephrine was assessed to investigate its metabolism across the lung. The measurements were performed in 34 mountaineers during both rest and exercise at low altitude and after 20 hours at high altitude (4559 m). Norepinehrine and epinephrine concentrations were measured by high-performance liquid chromatography. Pulmonary blood flow was assessed by inert gas rebreathing, and systolic PAP (PASP) by transthoracic Doppler-echocardiography. - Results - Exercise and high altitude increased PASP and increased arterial and central venous plasma norepinephrine. In contrast, exercise but not high altitude increased arterial and central venous epinephrine. There was no significant a − cvdiff for norepinephrine and epinephrine during rest and exercise at low altitude, nor during rest at high altitude. However, during exercise at high altitude the a − cvdiff for norepinephrine was positive. There was no correlation between the a − cvdiff of both norepinephrine and epinephrine with PASP during exercise, high altitude or during a combination of both. - Conclusions - The degree of pulmonary hypertension that occurs upon high-altitude exposure is largely independent of the SNS activity in the pulmonary vasculature and adrenal gland.